Study on the Extracts of Some Ornamental Plants on Germination and Seedling Growth of Pea (Global Journal of Science Frontier Research, 2017)
An experiment was conducted to study the effects of aqueous extracts of few ornamental plants viz. China box (Murraya exotica), Indian Medlar (Mimusopsel engi), Parrot tree (Buteamonosperma)Mussaenda (Mussaen daerythr -ephytta), Mast tree (Polyalthialongi folia) and Swamp tree (Swamp tree occidentalis) on the germination and growth of Pea (Pisumsativum). Mussaenda (Mussaendaerythrephytta) plant extract showed the highest percentage of germination and shoot length of pea and lowest percentage was found from aqueous extract of Indian Medllar (Mimusopselengi). The longest root length was found on control condition (water) and shortest found on Mussaenda (Mussaendaerythrephytta). The highest chlorophyll contents was found on Parrot tree (Buteam -onosperma)and lowest was found on Mussaenda (Mussaendaerythrephytta). So, it may be concluded that aqueous extract of Mussaenda (Mussaendaery -threphytta) is good for germination, growth and developments of pea (Pisumsativum).
Keywords: aqueous extract; germination; seedling growth; pea